New constraints on the geochronology and Sm-Nd isotopic characteristics of Bas-Drâa mafic dykes, Anti-Atlas of Morocco. (March 2017) - El Bahat, Abdelhakim; Ikenne, Moha; Cousens, Brian; Söderlund, Ulf; Ernst, Richard; Klausen, Martin B.; Youbi, Nasrrddine
Abstract: The Precambrian inliers of the Anti-Atlas belt across the southern part of Morocco contain numerous mafic dyke and sill swarms, which are thought to represent the erosional remnants of Proterozoic Large Igneous Provinces (LIPs). As part of an extended research campaign to date and characterize these LIPs, two amphiboles from one dyke within the Bas-Drâa inlier (western Anti-Atlas) yielded consistent 40 Ar- 39 Ar ages of 611 Ma ± 1.3; i.e., evidence of magmatic activity during the Ediacaran (635-542 Ma). Furthermore, Nd isotope ratios and model ages identifies four groups of dykes within the Bas-Drâa inlier, all of which were derived from a previously enriched mantle reservoir with very low 143 Nd/ 144 Nd ratios (0.51065–0.51170) and corresponding εNd(t) values (−16.44 to −2.45). Such low Nd-ratios arguably reflect either a contribution of crustal components, such as the Paleoproterozoïc schisto-granitic basement, or metasomatic modification of the sub-continental lithospheric mantle. Highlights: A new dyke has been dated by Ar-Ar method. Two amphiboles yielded consistent ages of 611 Ma ± 1.3 for one mafic from Bas-Drâa inlier. Sm-Nd isotopic ratios and model ages allow recognition of four groups of dykes in the Bas-Drâa inlier with different sources, all derived from a previously enriched mantle reservoir. The low 143 Nd/ 144 Nd and εNd(t) values reflect a low contribution of crustal components such as the Paleoproterozoïc schisto-granitic basement or metasomatic modification of the mantle.